Approach-avoidance modification as an add-on in smoking cessation: A randomized-controlled study. (March 2019) - Wittekind, Charlotte E.; Reibert, Evelyne; Takano, Keisuke; Ehring, Thomas; Pogarell, Oliver; Rüther, Tobias
Abstract: Biases in information processing are attributed an important role in the maintenance of tobacco dependence. As these biases are not sufficiently taken into account in current treatments, the aim of the present study was to investigate whether clinical outcome can be improved by combining treatment-as-usual (TAU) with Approach-Avoidance Modification Training (AAMT). A two group parallel (1:1) randomized-controlled single-blind study with adult smokers ( N  = 105) was conducted (DRKS00011406). Participants received three sessions of TAU and either six sessions of AAMT or Sham training. During AAMT, participants were trained to implicitly avoid all smoking-related and to approach all smoking-unrelated pictures, while the contingency was 50:50 in Sham training. Participants were assessed after the intervention and 6 months later. Primary outcome was daily cigarette consumption at follow-up. Participants receiving TAU + AAMT did not show a significantly greater reduction of daily cigarette consumption at follow-up compared to TAU + Sham (per-protocol: 95% CI: -2.56–4.89, p  = .608; intention-to-treat: 95% CI: -3.11–2.96, p  = .968). Using an implicit AAMT (vs. Sham) as an add-on to TAU did not improve clinical outcome. However, no consistent evidence for a change of bias was found. It is important for future research to explore the effectiveness of optimized training versions (e.g., explicit instructions). Pre-registration: German Clinical Trials Register (DRKS00011406). Highlights: Approach-avoidance training is effective as an add-on in alcohol dependence. This study combines treatment-as-usual (TAU) and avoidance-training in smoking. We conducted a single-blind RCT comparing the efficacy of TAU + AAMT vs. TAU + Sham. TAU + avoidance training did not improve clinical outcome.